2011
DOI: 10.4317/medoral.16.e514
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with early failure of dental implants. A literature review

Abstract: The aim of the study was to examine articles published on risk factors associated with early failure of dental implants. We conducted a search on PubMed for articles published between January 2000 and December 2009 using the keywords 'dental implants' and 'early failure'. Seven studies that specified the number of early failed implants and studied the associated risk factors were included. Early failures are caused by the inability of tissue to establish osseointegration prior to prosthetic restoration; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
2
14

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 11 publications
(45 reference statements)
5
54
2
14
Order By: Relevance
“…Despite the high success rates, 1,2 dental implant failure may occur and is defined as the inadequacy of the tissues to establish or maintain the osseointegration. 3,4 Bacterial-associated peri-implant infection is considered an inflammatory process affecting the tissues around the implant in function, resulting in loss of supporting bone, and is reported to be one of most important reasons causing dental implant failure. 5 The oral cavity is a complex microecological environment, and 6 after implantation, the bacteria can invade the peri-implant soft tissue and may potentially progress deeper into the bone and undermine the osseointegration process.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high success rates, 1,2 dental implant failure may occur and is defined as the inadequacy of the tissues to establish or maintain the osseointegration. 3,4 Bacterial-associated peri-implant infection is considered an inflammatory process affecting the tissues around the implant in function, resulting in loss of supporting bone, and is reported to be one of most important reasons causing dental implant failure. 5 The oral cavity is a complex microecological environment, and 6 after implantation, the bacteria can invade the peri-implant soft tissue and may potentially progress deeper into the bone and undermine the osseointegration process.…”
Section: Introductionmentioning
confidence: 99%
“…Reported success rates for oral implants are high; however, there is a lack of longitudinal data with at least 5 years of follow-up [2]. It has been suggested that several risk factors may impair long-term implant survival including jaw location (anterior vs. posterior region and maxilla vs. mandible) [3], implant dimensions (length, diameter, and implant design) [4], simultaneous or staged bone augmentation procedures [5], local bone density at the implant site [6], and patient-related risk factors such as age, smoking, history of periodontal disease, diabetes mellitus, and osteoporosis [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…The literature is divided as to whether advancing age is truly a risk factor for failure. 12,13 It has been suggested that with advancing age, there are changes in bone and collagen that may result in longer healing periods. An important note to make is that older patients may also have more alveolar bone atrophy, resulting in reduced bone volume and increasing the rate of failure.…”
Section: Discussionmentioning
confidence: 99%